Análise do desgaste oclusal e da densidade óssea alveolar de molares inferiores em dois sambaquis do litoral brasileiro - Marquez, Daniel Camacho (2012)
Occlusal surface wear and alveolar bone radiographic density of the mandibular first and second molars were assessed in 29 specimens of adult shellmound builders from two Brazilian sambaquis: Zé Espinho (N = 14) and Cabeçuda (N = 15). Tooth wear was categorized by the Scott’s method (1979) and the degree of mineralization in the alveolar bone was estimated on the histogram of digital images. Comparisons between sambaqui groups were carried out using ANOVA/Tukey test (α = 0.05). In the specimens from Zé Espinho, mean values for tooth wear varied between 4.54 ± 1.94 to 8.00 ± 1.84; whereas in those from Cabeçuda, varied between 5.46. ± 2.21 to 8.14 ± 1.56. Most specimens presented tooth wear with at least 25% of dentine exposure in one of the examined occlusal quadrants. Tooth wear was significantly accentuated in the first molars and specifically on the buccal quadrants, compared to the second molars and lingual quadrants, respectively, p < 0.001. In Zé Espinho sambaqui, the average bone density varied between 15.97 ± 3.7 to 23.72 ± 4.96, with higher mean values in the apical regions (24.23 ± 3.27 – 24.25 ± 4.29). In Cabeçuda sambaqui, the average bone density varied between 16.24 ± 5.28 to 18.60 ± 4.56, similarly with higher mean values in the apical regions (20.03 ± 5.88 – 20.19 ± 5.89). Bone density mean values were significantly higher in the apical regions compared to the regions bellow the crestal bone, p < 0.001. In Cabeçuda sambaqui, the average occlusal wear was significantly higher in comparison to the specimens from Zé Espinho (p < 0.001). Conversely, the average bone density was significantly lower in Cabeçuda than in Zé Espinho sambaqui (p < 0.001). It may be suggested that shellmound builders from the studied sambaquis presented different degrees of dental wear and alveolar bone density. One might speculate that the greater the occlusal wear, the lower the radiographic alveolar bone density.